DEEP LEARNING DALAM PEMBELAJARAN MATEMATIKA DI SD - Maharani, Lily; Arie Rakhmat Riyadi; Neni Maulida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics learning at the elementary school (SD) level still faces various challenges. One of the main challenges is the low interest and understanding of students toward mathematical concepts taught through conventional methods. Teaching approaches that tend to be mechanistic and memorization-based often make it difficult for students to deeply understand concepts and apply them in everyday life. To build meaningful understanding (deep learning), students need to be fully present cognitively, affectively, and metacognitively during the learning process. The concept of mindfulness can serve as an approach to encourage students to be more present and engaged in the learning process.The data in this study were collected from articles that met the inclusion and exclusion criteria described in the research methodology, and were filtered using Publish or Perish. Based on a literature review of 10 articles, it was found that the deep learning approach has a positive impact on students’ understanding, fostering critical, creative, and analytical thinking skills. The results of this research are expected to contribute to the development of more meaningful mathematics learning practices that focus on conceptual understanding for elementary school students.